1977
DOI: 10.1037/0022-3514.35.7.485
|View full text |Cite
|
Sign up to set email alerts
|

Social roles, social control, and biases in social-perception processes.

Abstract: To make accurate social judgments, an individual must both recognize and adequately correct for the self-presentation advantages or disadvantages conferred upon actors by their social roles. Two experiments examined social perceptions formed during an encounter in which one participant composed difficult general knowledge questions and another participant attempted to answer those questions. It was found, as predicted, that perceivers fail to make adequate allowance for the biasing effects of these "questioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
174
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(189 citation statements)
references
References 11 publications
12
174
0
3
Order By: Relevance
“…We found that when people know they have been observed engaging in situationally constrained behavior, they overestimate the extremity of observers' dispositional inferences about them (Savitsky, Epley, & Gilovich, 2001;Van Boven, Kamada, & Gilovich, 1999; see also Miller, Baer, & Schonberg, 1979). In one study, people who were assigned the role of contestant in a quiz show, whose performance was constrained by the disadvantageous position of being tested on another person's idiosyncratic repertoire of trivia (Ross, Amabile, & Steinmetz, 1977), overestimated how harshly others would judge them (Savitsky et al, 2001, Study 3).…”
mentioning
confidence: 84%
“…We found that when people know they have been observed engaging in situationally constrained behavior, they overestimate the extremity of observers' dispositional inferences about them (Savitsky, Epley, & Gilovich, 2001;Van Boven, Kamada, & Gilovich, 1999; see also Miller, Baer, & Schonberg, 1979). In one study, people who were assigned the role of contestant in a quiz show, whose performance was constrained by the disadvantageous position of being tested on another person's idiosyncratic repertoire of trivia (Ross, Amabile, & Steinmetz, 1977), overestimated how harshly others would judge them (Savitsky et al, 2001, Study 3).…”
mentioning
confidence: 84%
“…In their experiment, actors made attributions to the environment while observers made dispositional attributions to the actor. Ross, Amabile, and Steinmetz (1977) extended this work with a "Quiz Show" study. Undergraduate observers made attributions of higher intelligence to a questioner than to the answerer even though the situation overwhelmingly favored the question asker.…”
Section: Task Featuresmentioning
confidence: 99%
“…One of the most interesting studies of attribution error is by L. Ross, Amabile, and Steinmetz (1977). Compared to most research in this area, the situation it created for subjects was unusually realistic.…”
Section: Social Rolesmentioning
confidence: 99%